Comparing the Effectiveness of Artificial Intelligence Models in Predicting Ovarian Cancer Survival: A Systematic Review - Farkhondeh Asadi; Milad Rahimi; Nahid Ramezanghorbani; Sohrab Almasi (Cancer Reports)
ABSTRACT Background This systematic review investigates the use of machine learning (ML) algorithms in predicting survival outcomes for ovarian cancer (OC) patients. Key prognostic endpoints, including overall survival (OS), recurrence‐free survival (RFS), progression‐free survival (PFS), and treatment response prediction (TRP), are examined to evaluate the effectiveness of these algorithms and identify significant features that influence predictive accuracy. Recent Findings A thorough search of four major databases—PubMed, Scopus, Web of Science, and Cochrane—resulted in 2400 articles published within the last decade, with 32 studies meeting the inclusion criteria. Notably, most publications emerged after 2021. Commonly used algorithms for survival prediction included random forest, support vector machines, logistic regression, XGBoost, and various deep learning models. Evaluation metrics such as area under the curve (AUC) (18 studies), concordance index (C‐index) (11 studies), and accuracy (11 studies) were frequently employed. Age at diagnosis, tumor stage, CA‐125 levels, and treatment‐related factors were consistently highlighted as significant predictors, emphasizing their relevance in OC prognosis. Conclusion ML models demonstrate considerable potential for predicting OC survival outcomes; however, challenges persist regarding model accuracy and interpretability. Incorporating diverse data types—such as clinical, imaging, and molecular datasets—holds promise for enhancing predictive capabilities. Future advancements will depend on integrating heterogeneous data sources with multimodal ML approaches, which are crucial for improving prognostic precision in OC.